Rare cause of coronary artery ectasia in children: A case report of methylmalonic acidemia with hyperhomocysteinemia - Juan, Tu; Chao-ying, Chen; Hua-rong, Li; Ling, Wan (Frontiers in Pediatrics, 2022)
Background Methylmalonic acidemia (MMA) with hyperhomocysteinemia is caused by cobalamin deficiency, mainly due to disturbance of cobalamin C (cblC) metabolism. Its clinical manifestations involve many organs. However, cases of coronary artery ectasia have been rarely reported. Case presentation Here, we report the case of a 4-year-old girl who was hospitalized mainly because of pallor, brown urine, and fatigue, followed by hypertension, renal insufficiency, hemolytic anemia, cardiac enlargement, cardiac insufficiency, and coronary artery ectasia. Thrombotic microangiopathy (TMA) was confirmed by renal pathological examination. Metabolic examination showed hyperhomocysteinemia and methylmalonic aciduria. Furthermore, genetic assessment confirmed MMACHC gene variant, which confirmed the final diagnosis of a cblC defect. Intramuscular injection of hydroxy-cobalamin, oral medications of betaine, levocarnitine，folic acid and aspirin were administered. Three months later, the patient's condition was significantly improved. Anemia was corrected, and the renal function was normal. Heart size, cardiac function, and coronary artery structure completely returned to normal. Conclusion The clinical manifestation of cblC deficiency is atypical. This critical condition may be associated with multiple organ involvement. A rare complication, coronary artery ectasia, can also occur. Early identification, careful evaluation, and appropriate treatment are crucially important for the improvement of this disease prognosis.